Quality and educational innovation for Certificates of Pedagogical Aptitude: Repercussion and impact on the improvement of educational quality - Barrio de la Puente, José Luis (Pulso. Revista de educación, 2004)
This article, first, outlines the historical evolution of the concept of 'quality' and subsequently analyses the significance of formative quality, and then, educational quality in contemporary society. The article proceeds to analyse the determining factors that influence the quality of educational institutions and organisations, highlighting their significance in training entities, with a particular emphasis on Teacher Support Centres. Moreover, these organisations pinpoint the primary reference points for training quality that must be incorporated into any Spanish Certificate of Pedagogical Aptitude (CAP) training plan, along with identifying the most effective training strategies for teachers and advisers. The article concludes by emphasising the necessity of pursuing continuous improvements in the CAP by implementing the recommendations proposed for a quality level of training.